How French alternative media channels on YouTube portray the government and mainstream media on YouTube - Reveilhac, Maud; Nchakga, Camille (Frontiers in Communication, 2025)
In an increasingly fragmented media landscape, YouTube has become a pivotal platform for alternative media channels that challenge mainstream media and governmental narratives. This study investigates how French alternative media channels on YouTube shape their identities and discourse regarding the government. The study analyzes content from these channels to understand their impact on the media ecosystem. Using word embedding and correspondence analysis, the study reveals a strong antagonistic stance toward mainstream media and government. Findings show that alternative media channels function as new gatekeepers, using decentralized mechanisms to disseminate information, thus redefining traditional gatekeeping roles. They simultaneously provide factual content and amplify skeptical narratives, contributing to public mistrust in journalism and governmental institutions. The implications are discussed along the evolving role of alternative media in shaping public perceptions and the need for ongoing research to capture these complex interactions in an ever-changing media landscape.